THE INFLUENCE OF CURRENT RATIO (CR), TOTAL ASSET TURN OVER (TATO), DEBT TO EQUITY RATIO (DER), NET PROFIT MARGIN (NPM) ON PROFIT GROWTH IN PT. ULTRAJAYA MILK & TRADING COMPANY, TBK - Arimi, Kurnia; Alwi, Alwi; Muthiah, Hanifah (Universitas Riau Kepulauan, 2024)
An alternative to predicting profit growth, including future financial conditions, is to carry out financial ratio analysis. The ratios used in this research include liquidity, activity, leverage and profitability ratios. The purpose of this research is to determine the Current Ratio (CR), Total Asset Turn Over (TATO), Debt To Equity Ratio (DER), Net Profit Margin (NPM) on profit growth at PT. Ultrajaya Milk & Trading Company, Tbk. The research instrument used is a list of tables consisting of data on current assets, current liabilities, sales, total assets, total debt, total equity and net profit for the current year and net profit for the previous year. The population in this research is the financial statements of PT. Ultrajaya Milk & Trading Company, Tbk has been listed on the IDX from 1990 to 2022, which is 32 years. The sample in this research is the financial report of PT. Ultrajaya Milk & Trading Company, Tbk for 10 years, namely from 2013 to 2022. The sampling technique used in this research was purposive sampling. Research data was collected by means of documentation and literature study and then analyzed by hypothesis testing, t test and f test. The research results show that the Current Ratio (CR), Total Asset Turn Over (TATO), Debt To Equity Ratio (DER) and Net Profit Margin (NPM) have a partial and simultaneous effect on profit growth at PT. Ultrajaya Milk & Trading Company, Tbk.